True pylorus duplication: a case report - Mandora, Hala H.; Al Nafisah, Turki I.; Bamajboor , Abdullah Y. (International Surgery Journal, 2024)
True pylorus duplication cysts are particularly rare, the literature describes only a small number of cases. They account for nearly 2.2% of all alimentary tract duplications. Most of the gastric duplications presents at an age younger than one year with one-third diagnosed in the neonatal period. However, they are not limited to that period. We report a case of a true pyloric duplication cyst in a 3-year-old girl who had been experiencing frequent vomiting with occasional abdominal pain for about 15 days prior to her presentation. The patient had an abdominal ultrasound that showed an epigastric cystic mass. CT of the abdomen demonstrated a 3.8×3.8 cm mass with a claw sign proximal to the first part duodenum. The diagnosis of pyloric duplication cyst was confirmed during the operation and with the histopathological examination following the resection. The patient is doing well with an appropriate weight gain at the follow-up appointments. The patient is doing well with an appropriate weight gain at the follow-up appointments. In summary, this is an an unusual case of gastric outlet obstruction that presented outside the usual age period caused by a pyloric duplication cyst. Imaging studies including US and CT are useful aids in the diagnoses of gastrointestinal duplication cysts.